Expression of Duodenal Iron Transporter Proteins in Diabetic Patients with and without Iron Deficiency Anemia. (6th March 2018) - Broide, Efrat; Reifen, Ram; Matalon, Shay; Berkovich, Zipi; Shirin, Haim
Abstract : The role of iron transport proteins in the pathogenesis of anemia in patients with diabetes mellitus (T2DM) is still unclear. We investigated the expression of duodenal transporter proteins in diabetic patients with and without iron deficiency anemia (IDA). Methods . Overall, 39 patients were included: 16 with T2DM and IDA (group A), 11 with T2DM without IDA (group B), and 12 controls (group C). Duodenal mucosal expression of divalent metal transporter 1 (DMT1), ferroportin 1 (FPN), hephaestin (HEPH), and transferrin receptor 1 (TfR) was evaluated by Western blotting. Chronic disease activity markers were measured as well. Results . FPN expression was increased in group A compared to group B and controls: 1.17 (0.72–1.46), 0.76 (0.53–1.04), and 0.71 (0.64–0.86), respectively (p = 0.011 ). TfR levels were over expressed in groups A and B compared to controls: 0.39 (0.26–0.61), 0.36 (0.24–0.43), and 0.18 (0.16–0.24), respectively, (p = 0.004 ). The three groups did not differ significantly with regard to cellular HEPH and DMT1 expression. The normal CRP and serum ferritin levels, accompanied with normal FPN among diabetic patients without IDA, do not support the association of IDA with chronic inflammatory state. Conclusion . In patients with T2DM and IDA, duodenal iron transport protein expression might be dependent on body iron stores rather than by chronic inflammation or diabetes per se.